The impact of wetland on neutral mine drainage from mining wastes at Luanshya in the Zambian Copperbelt in the framework of climate change - Sracek, Ondra; Kříbek, Bohdan; Mihaljevič, Martin; Ettler, Vojtěch; Vaněk, Aleš; Penížek, Vít; Filip, Jan; Veselovský, František; Nyambe, Imasiku (Environmental science and pollution research international, 2018)
The impact of a natural wetland ("dambo" in Zambia) on neutral mine drainage at Luanshya in the Zambian Copperbelt has been investigated during an intermediate discharge period (July) using a multi-method characterization of solid phase samples, sequential extraction analysis, X-ray diffraction, Mössbauer spectroscopy, and scanning electron microscopy combined with water analyses, isotopic analyses, and geochemical modeling. In the wetland, the principal identified solid phases in sediments were carbonates, gypsum, and ferric oxyhydroxides. A significant portion of the ochres was present as insoluble hematite. Mine drainage pH values decrease, and log [Formula: see text] values increase after inflow of water into the wetland; dissolved and suspended concentrations of Fe, Mn, Cu, and Co also decrease. Based on speciation calculations, there is no precipitation of secondary Cu and Co minerals in the period of sampling, but it can occur later in dry period when the flow rate is reduced. Concentrations of sulfate decrease, and values of δ34S(SO4) in the wetland increase in parallel, suggesting sulfate reduction is occurring. In more advanced dry period, the discharge in mine drainage stream is probably much lower and water can reach supersaturation with respect to minerals such as gypsum, which has been found in sediments. Wetlands have a positive impact on mine drainage water quality due to the removal of metals by adsorption, co-precipitation, and filtration of colloids. However, there can also be a rebound of contamination by seepage inflow downstream from the wetland. Ongoing climate change with extreme hydrologic events may enhance differences between dry and rainy seasons with resulting faster mobilization of contaminants.
Keywords: Minerals; Carbonates; Environmental Monitoring; odpadní voda; mokřady; roční období; sírany; X-Ray Diffraction; Mining; síran vápenatý; Chemical Precipitation; těžké kovy; chemická precipitace; Calcium Sulfate; Seasons; adsorpce; Zambie; filtrace; Wetlands; difrakce rentgenového záření; Weather; Adsorption; Climate Change; koloidy; železité sloučeniny; minerály; Ferric Compounds; Zambia; počasí; klimatické změny; hornictví; Sulfates; Filtration; Water Pollutants, Chemical; chemické látky znečišťující vodu; Wastewater; monitorování životního prostředí; Metals, Heavy; uhličitany; Colloids